Haploinsufficient TNAP Mice Display Decreased Extracellular ATP Levels and Expression of Pannexin-1 Channels - Sebastián-Serrano, Álvaro; de Diego-García, Laura; Henshall, David C.; Engel, Tobías; Díaz-Hernández, Miguel (Frontiers in Pharmacology, 2018)
Hypophosphatasia (HPP) is a rare heritable metabolic bone disease caused by hypomorphic mutations in the ALPL (in human) or Akp2 (in mouse) gene, encoding the tissue-nonspecific alkaline phosphatase (TNAP) enzyme. In addition to skeletal and dental malformations, severe forms of HPP are also characterized by the presence of spontaneous seizures. Initially, these seizures were attributed to an impairment of GABAergic neurotransmission caused by altered vitamin B6 metabolism. However, recent work by our group using knockout mice null for TNAP (TNAP-/-), a well-described model of infantile HPP, has revealed a deregulation of purinergic signaling contributing to the seizure phenotype. In the present study, we report that adult heterozygous (TNAP+/-) transgenic mice with decreased TNAP activity in the brain are more susceptible to adenosine 5′-triphosphate (ATP)-induced seizures. Interestingly, when we analyzed the extracellular levels of ATP in the cerebrospinal fluid (CSF), we found that TNAP+/- mice present lower levels than control mice. To elucidate the underlying mechanism, we evaluated the expression levels of other ectonucleotidases, as well as different proteins involved in ATP release, such as pannexin, connexins and vesicular nucleotide transporter (VNUT). Among these, Pannexin-1 (Panx1) was the only one showing diminished levels in the brains of TNAP+/- mice. Altogether, these findings suggest that a physiological regulation of extracellular ATP levels and Panx1 changes may compensate for the reduced TNAP activity in this model of HPP.